1999
DOI: 10.1292/jvms.61.621
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Activity, and Neurofilament Protein, and Catecholamine Synthesizing Enzymes Immunoreactivities in the Mouse Adrenal Gland during Postnatal Development.

Abstract: ABSTRACT. The present study showed the acetylcholinesterase (AChE) activity, and neurofilament protein (NFP), catecholaminesynthesizing enzymes, dopamine β-hydroxylase (DBH) and phenylethanolamine N-methyltransferase (PNMT) immunoreactivities in the mouse adrenal gland during postnatal development. From birth to postnatal-1-day, AChE activity was weakly and diffusely found in some medullary cells and in very few nerve fibers whereas strong NFP immunoreactivity was seen in a few ganglion cells and in remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…It is noteworthy that not only basal but also evoked E release is much larger than NE release. This is consistent with the fact that mouse chromaffin cells mainly exhibit an adrenergic phenotype (80% of epinephrine-containing cells 16 ).…”
Section: Resultssupporting
confidence: 89%
“…It is noteworthy that not only basal but also evoked E release is much larger than NE release. This is consistent with the fact that mouse chromaffin cells mainly exhibit an adrenergic phenotype (80% of epinephrine-containing cells 16 ).…”
Section: Resultssupporting
confidence: 89%
“…Other study has shown that AChE-active nerve fibers were found in large numbers and preferentially innervated NA cells rather than A cells in the mouse adrenal medulla [8]. However, the present study did not show such preferential innervation to NA cells and A cells in the rat adrenal medulla by SP-immunoreactive nerve fibers until postnatal week 2.…”
Section: Discussioncontrasting
confidence: 89%
“…These results indicated the possibility that the functional innervation with SP-immunoreactive nerve fibers in the rat adrenal medulla was incomplete at postnatal week 3. Other studies have demonstrated that the number of AChE-active or AChE-immunoreactive nerve fibers reached the numbers observed in adults on postnatal day 16 or postnatal week 3 [6,8]. Furthermore, we demonstrated that the dense networks of SP-immunoreactive nerve fibers in the medulla surrounded the clusters of NA cells but not A cells from postnatal week 3 onward.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The process of CC segregation within the adrenal medulla is closely associated with the differential innervation between homophenotypic noradrenergic and adrenergic clusters, thus promoting the differential adrenaline secretion response to neural stimuli [33,34,35]. During postnatal development, AChE activity was preferentially observed in nerve fibres in contact with CC clusters in the rat adrenal medulla [34].…”
Section: Discussionmentioning
confidence: 99%